Entrepreneurial investment and lending crowdfunding: implications for regional development - Bernardino, Susana (2019)
Entrepreneurship is recognised as an important driver for economic growth. However, financing has been recognized as one of the most significant barriers to entrepreneurship. By analysing the operations of a lending crowdfunding platform in Portugal (Raize), the investigation aims to study the potential contribution of CF for regional development. Based on a database of 811 completed CF operations, the research uses a quantitative method. The results reveal that small organisations are especially prone to use CF as a financing strategy, regardless of its seniority, as well as ventures that have a moderated risk profile. However, coastal regions have been more dynamic on CF use than interior located ventures, since most of the operations were realized on the littoral of the country. The results suggest that interior organisations that use CF could have more financing difficulties that led them to look for new fundraising solutions, since they typically have higher size than coastal located organisations, although the risk rating is quite similar. The CF loans period is also shorter. The average interest rate charged is quite similar between both type of locations, although a higher variability exists in the funding conditions of interior organisations. The average offer per investor is also higher in the interior case.